Association of Second Hand Smoke and Biomass Cooking Fuel with the Tuberculosis: A Case-Control Study from Southern Haryana, India - Vipin Goyal; Abhishek Singh; Vikas Gupta; Sanjeet Panesar; Pawan Kumar Goel; Deepika Agrawal (Journal of Krishna Institute of Medical Sciences University, 2021)
Background: Cooking smoke is a known risk factor for a number of respiratory diseases. It is essential to delineate the role of these environmental factors in the etiology and epidemiology of Tuberculosis (TB). Aim and Objectives: The present study was conducted with an aim to assess the association of TB among the study subjects using biomass fuels for cooking or exposed to Second Hand Smoke (SHS). Material and Methods: The present case control study was conducted in the Department of Chest and TB for a duration of one-year and included 100 cases (new pulmonary TB) subjects and 300 controls as non-TB subjects who attended outpatient clinic. Data were collected as a structured questionnaire. Categorical data were presented as percentages (%) and bivariable logistic regression analysis was done to find out the strength of association between dependent variable and independent variables and an association was considered significant if the p value was less than 0.05. Results: There was more representation of male participants (53.6%) compared to females and 63.9% of participants were residing in the rural area. On comparative analysis for occurrence of TB among cases and controls, the statistically significant difference was observed for the variables such as age, overcrowding, biomass as cooking fuel, second hand smoke, socioeconomic status, and previous history of TB (p<0.05). Conclusion: Improvement in the standard of living brought about by economic development will lead to more people using cleaner fuels for cooking than biomass fuel which in turn will lead to a reduction in the occurrence of pulmonary TB in the community.